Timing of prooxidant and antioxidant intake shapes life-history and parasite tolerance in Anopheles mosquitoes - Zeferino, Tiago G.; Mora, Alfonso Rojas; Koella, Jacob C. (Frontiers in Ecology and Evolution, 2025)
IntroductionOxidative homeostasis plays a crucial role in physiology, as reactive oxygen species (ROS) regulate immunity and longevity, but also lead to damaging oxidative stress. ROS are therefore expected to influence host-parasite interactions. Previous studies have shown that supplementing mosquito diets with prooxidants (hydrogen peroxide) or antioxidants (ascorbic acid) disturbs their oxidative balance, particularly in uninfected individuals, which actively avoid these compounds when given a choice.MethodsHere, we evaluated how such diet-induced shifts in oxidative status influence infection outcomes with the microsporidian parasite Vavraia culicis in the mosquito Anopheles gambiae. Mosquitoes were fed a standard sugar solution or one supplemented with a prooxidant or an antioxidant either early or late in life. We then measured longevity, fecundity, and parasite load 13 days after emergence or at death.ResultsEarly prooxidant consumption increased longevity; this benefit was lower in infected mosquitoes. Antioxidant consumption increased fecundity irrespective of infection. Early intake of either supplement increased parasite load in 13-day old mosquitoes, while late intake promoted parasite growth later in life.DiscussionThese findings reveal context-dependent effects of oxidative status on host traits and parasite dynamics, emphasizing the crucial role of timing in shaping oxidative interventions.